2016
DOI: 10.1016/j.paid.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Shaping aggressive personality in adolescence: Exploring cross-lagged relations between aggressive thoughts, aggressive behaviour and self-control

Abstract: Aggressive ideations can be defined as thoughts, daydreams or fantasies of harming another. They feature in theoretical models of aggressive behaviour causation and are used in violence risk assessments. Little is known, however, about long term relations between aggressive ideations, aggressive behaviour and related variables such as self-control. We examined cross-lagged associations between these variables in the most recent two waves of the Zurich project on social development (z-proso) when the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
4
25
0
1
Order By: Relevance
“…Past research has suggested that the tendency to report violent ideations is quite stable over adolescence (e.g. Murray et al, 2016e); however, whether this stability and the pattern of relations between violent ideations and mental health dimensions are maintained into adulthood is not yet clear. Finally, the fact that violent ideations and mental health dimensions were measured with different albeit identically formatted and administered inventories, could have reduced their covariance with other mental health dimensions relative to the covariance among mental health dimensions.…”
Section: Discussionmentioning
confidence: 98%
“…Past research has suggested that the tendency to report violent ideations is quite stable over adolescence (e.g. Murray et al, 2016e); however, whether this stability and the pattern of relations between violent ideations and mental health dimensions are maintained into adulthood is not yet clear. Finally, the fact that violent ideations and mental health dimensions were measured with different albeit identically formatted and administered inventories, could have reduced their covariance with other mental health dimensions relative to the covariance among mental health dimensions.…”
Section: Discussionmentioning
confidence: 98%
“…Previous empirical research examining the possibility that the association between self-regulation and aggressive behavior is bidirectional in adolescence comes from the criminology domain (de Kemp et al, 2009;Murray et al, 2016). As suggested by Ge and Conger (1999), the reciprocal relation between self-control and aggressive behavior might reflect a dynamic personality development process:…”
Section: Discussionmentioning
confidence: 99%
“…In turn, rumination is closely associated at the cognitive level with another potentially transdiagnostic variable, such as violent ideation. It has presented significant associations with different mental health problems such as reactive, physical and proactive aggression [33], especially as a predictor in cases of poor self-control; however, it is not yet clear if violent ideation reflects the aggressive manifestation and not a causal variable [57] (Table 4). However, studies are inconclusive and require differentiation in terms of negative content and anger, particularly when closely linked to different psychopathologies, violent acts, and a general deterioration of mental health [58].…”
Section: Emotional Dysregulation Motivation and Cognitionmentioning
confidence: 99%